Penentuan Aktivitas Antioksidan dan Kandungan Flavonoid Total Ekstrak Daun Papasan (Coccinia grandis L.) Berdasarkan Perbedaan Pelarut Polar : Determination of Antioxidant Activity and Total Flavonoid Contents Extract of Papasan Leaves (Coccinia grandis L.) Based on The Differences Polar Solvents - Meliani Sari; Rani Nareza Ulfa; Mauritz Pandapotan Marpaung; Purnama (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2021)
Papasan leaves have several properties, including antihyperglycemic, diabetes, antipyretic and antioxidant. Minor metabolite compounds that have the potential as antioxidants from this plant are flavonoids, alkaloids, saponins, and tannins. This study's purpose to determine the antioxidant activity and the flavonoid total contents of Papasan (Coccinia grandis L.) leaf extract based on the differences in polar solvents. The polar solvents used were ethanol, methanol, and water. Extraction used by maceration and dekokta. The antioxidant activity and the flavonoid total contents were established by UV-Vis spectrophotometry according to the decrease in absorbance at a maximum wavelength of 515 nm by the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. Determination of antioxidant activity and the flavonoid total contents were excluded on quercetin comparisons. The values of IC50 and the flavonoid total contents in the ethanol extract respectively were 287.92 ppm and 49.825 mg QE/g while the IC50 values and total flavonoid levels in the extract of methanol were 73.29 ppm and 50.415 mg QE/g. In the extract of the water, the value of IC50 was 39.80 ppm and the total flavonoid contents were 50.415 mg QE/g. The conclusions of these studies were that the most antioxidant activity was found in water extract, while water and methanol extract had the same and highest levels of total flavonoids.